2008
DOI: 10.4049/jimmunol.181.3.1898
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cells Confer Lymph Node-Specific Properties by Shaping a Unique Microenvironment Influencing Local Immune Responses

Abstract: Lymph nodes (LN) consist not only of highly motile immune cells coming from the draining area or from the systemic circulation, but also of resident stromal cells building the backbone of the LN. These two cell types form a unique microenvironment which is important for initiating an optimal immune response. The present study asked how the unique microenvironment of the mesenteric lymph node (mLN) is influenced by highly motile cells and/or by the stromal cells. A transplantation model in rats and mice was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 48 publications
6
86
0
Order By: Relevance
“…A strong IgA response in the intestine can be induced by oral administration of cholera toxin (CT), which is known to be one of the most potent mucosal immunogens. 9,[22][23][24] CT is also used as an adjuvant. 25 In this study, the mLNs of rats were removed and orally administered CT was used as an example of an immunogen in the gut-associated lymphoid tissue (GALT).…”
Section: Discussionmentioning
confidence: 99%
“…A strong IgA response in the intestine can be induced by oral administration of cholera toxin (CT), which is known to be one of the most potent mucosal immunogens. 9,[22][23][24] CT is also used as an adjuvant. 25 In this study, the mLNs of rats were removed and orally administered CT was used as an example of an immunogen in the gut-associated lymphoid tissue (GALT).…”
Section: Discussionmentioning
confidence: 99%
“…1). In LN transplantation experiments, where the hematopoietic cells of the LN were completely replaced by host cells while the stromal compartments remained donor derived, the specific T cell homing responses induced were those of the original location, rather than the transplanted location [9,69,85]. Additionally, while removal of the cervical LN blocked the induction of musosal tolerance, rescue could be achieved by transplanting a donor cervical LN but not mesenteric or peripheral LNs [86].…”
Section: Lymphoid Organs In Peripheral Tolerancementioning
confidence: 99%
“…This study suggested that RA-producing stromal cells and DCs in MLN warrant the gut-tropism of activated T cells in the musoca area (131). In one elegant study of implanting MLN and peripheral LN fragments into the mesenteric region of host rat and mouse, it was established that stromal cells in MLN but not in peripheral LN provided a unique microenvironment allowing for the acquisition of a gut-tropism phenotype of T and B cells during antigen-induced activation (3,72). In addition to gut mucosa, CD103…”
Section: A Ra Synthesis In the Gutmentioning
confidence: 98%
“…Some studies have revealed the role of RA in maintaining the immune tolerant microenvironment in the eye through inhibition of Th1/Th17 response and promotion of Treg development. Immunization of C57BL/6 mice with human interphotoreceptor retinoid binding protein peptide 1 to 20 [IRBP (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) ] elicited experimental autoimmune uveoretinitis (EAU). Keino et al (95) reported that intraperitoneal RA administration dampened the severity of EAU when administrated at 200 g/mouse (Ïł20-fold above normal sera RA concentration, every other day) before the disease onset.…”
Section: Ra Regulates Uveitismentioning
confidence: 99%